2020
DOI: 10.1113/ep088780
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the lncRNA AFAP1‐AS1/microRNA‐195/E2F3 axis in proliferation and migration of enteric neural crest stem cells of Hirschsprung's disease

Abstract: New Findings What is the central question of this study?Long non‐coding RNAs (lncRNAs) are widely involved in the progression of Hirschsprung's disease (HSCR), but the role of actin filament associated protein 1 antisense RNA1 (AFAP1‐AS1), an lncRNA, in HSCR has not been explored before. What is the main finding and its importance?Downregulation of AFAP1‐AS1 blocks enteric neural crest stem cell proliferation, differentiation, migration and invasion and promotes the occurrence of HSCR via the miR‐195/E2F3 axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…E2F3, E2F3a, and E2F3b exert synergistic or antagonistic roles in tumorigenesis and progression (18,19). Dysregulation of E2F3 expression is linked to diverse diseases, such as age-related cataracts (20) and Hirschsprung's disease (21). Additionally, E2F3 has been implicated in the development of diverse tumors as oncogenes.…”
Section: ' Discussionmentioning
confidence: 99%
“…E2F3, E2F3a, and E2F3b exert synergistic or antagonistic roles in tumorigenesis and progression (18,19). Dysregulation of E2F3 expression is linked to diverse diseases, such as age-related cataracts (20) and Hirschsprung's disease (21). Additionally, E2F3 has been implicated in the development of diverse tumors as oncogenes.…”
Section: ' Discussionmentioning
confidence: 99%
“…For instance, lncRNA AFAP1-AS acts as a ceRNA by enhancing miR-181a expression through competitively binding, which in turn eventually block the ENCCs migration and invasion [ 66 ]. Further exploring this relationship, Pan et al [ 67 ] discovered that in HSCR patients' diseased intestinal sections, the reduced expression of lncRNA AFAP1-AS1 leads to decreased proliferation, migration, and invasive capacities of enteric neural crest stem cells (ENCSCs). hey also found that lncRNA AFAP1-AS1 can interact with miR-195 through the ceRNA mechanism, specifically regulating the expression of its target gene E2F3, thereby affecting the activity of ENCSCs.…”
Section: Non-coding Rna Classes Associated With Hscrmentioning
confidence: 99%
“…In HSCR, both miRNA-200a and lncRNA AFAP1-AS1 have been proven to be related to the occurrence of HSCR [ 29 , 67 ]. However, comprehensive research on the function of proteins or peptides encoded by miRNA-200a and lncRNA AFAP1-AS1 in HSCR is still scarce.…”
Section: Non-coding Rna Classes Associated With Hscrmentioning
confidence: 99%
“…In addition, lncRNA DRAIC was found to regulate cell proliferation and migration in HSCR by affecting the miR-34a-5p/ITGA6 pathway ( 11 ). The silence of AFAP1-AS1 promoted HSCR progression by acting as an endogenous RNA to absorb miR-195 ( 12 ). Moreover, LOC100507600 is proved to participate in the development of HSCR through regulating BMI1 expression in a miR128-1-3p–dependent manner ( 13 ).…”
Section: Introductionmentioning
confidence: 99%